Analyzing the Issues of Science Learning Media on the Topic of States of Matter in Elementary Schools - Santi, Yulia; Muhibuddin; Armansyah, Teuku; Idayani, Vera; Yuliana; Yusniah; Susanti, Yenni; Mutiasari, Intan; Azuryati (Yayasan Citra Dharma Cindekia, 2024)
The aim of this research is to evaluate the problems faced in the use of science learning media, especially material material, at the elementary school level. This research uses a qualitative descriptive method and uses data collection methods such as observation, interviews and documentation studies. The research involved fourth grade teachers from five elementary schools in Bandar Baru District. The results of the research show several main problems, namely: (1) limited number of concrete learning media that can show changes in the shape of objects, (2) little variation in learning media that can show abstract concepts about the characteristics of solid, liquid and gas objects, and (3 ) little use of technology-based learning media to help understanding (4) Teachers' difficulties in developing learning media that suit the characteristics of the material and elementary school students, and (5) The use of learning media is not yet optimal in facilitating active and exploratory learning. Recommendations from this research include: procurement of adequate learning media, training in developing innovative learning media for teachers, as well as optimizing the use of learning media in the science teaching and learning process in elementary schools.